Effects of Ramadan Fasting on Sleep and Physical Fitness among Young Female Handball Players - Mohamed Alaeddine Guembri; Ghazi Racil; Mohamed Tounsi; Chirine Aouichaoui; Luca Russo; Gian Mario Migliaccio; Yassine Trabelsi; Nizar Souissi; Johnny Padulo (MDPI AG, 2024)
Objectives: This study examines the potential impact of Ramadan fasting on sleep patterns and physical fitness in under 14 (U14) and under 17 (U17) female handball players. Methods: For this study, sixty-five female handball players' (U14, n = 33 and U17, n = 32) sleep habits were assessed before (BR) and during the first (R1) and last weeks (R4) of Ramadan using: the Pittsburgh Sleep Quality Index (PSQI), the Insomnia Severity Index (ISI), and the Epworth Sleepiness Scale (ESS). Physical ability tests including balance and jumps were conducted throughout these periods.; Results: During Ramadan, both groups noted significant increases in PSQI and ISI scores during R1 (p < 0.01 and p < 0.05, respectively) and R4 (p < 0.05 and p < 0.05, respectively) compared to before Ramadan (BR). For the U14 group, a significant increase occurred in ESS scores during R1 (p < 0.01) and R4 (p < 0.05), whereas for the U17 group, this increase was limited over the R1 period (p < 0.05). In contrast, for all physical ability parameters, both groups showed no significant difference during R1 and R4; Conclusions: During adolescence, Ramadan fasting may alter sleep patterns in young female athletes but appears to have no effect on their performance in short-duration exercises.